Areas and Methods of Audiovisual Translation Research 2nd Revised Edition - Bogucki, Lukasz; Bogucki, Lukasz (Peter Lang, 2015)
This little gem offers the reader an overview of the various practices that form part of the ever increasing field of audiovisual translation (AVT) and makes brave inroads into the less glamorous but definitely needed areas of theory and research. Covering a wide range of topics in research in AVT, and admittedly questioning whether a universal methodology for audiovisual translation research is feasible, this volume theorises about the nature of AVT, helps to frame some of the current trends, and points to potentially new research avenues. The style is reader friendly and to the point; a most welcome addition to translation studies.Jorge Díaz Cintas, University College London